Cuidados paliativos para pacientes em estado terminal em Unidades de Terapia Intensiva: revisão sistemática e metanálise - Martins, Belmira Di Carla Paes Cardoso Cagliari [UNESP] (2016)
Introduction: The palliative care (PC) procedure is associated with better quality of life for terminally ill patients (TIP), in order to reduce the suffering of everyone involved in the death process. Rationale: it is believed that TIP should not be admitted nor die in the ICU. Objectives: To determine if the installation of CP teams can reduce the length of stay and mortality in ICU TIP. Methods: A Systematic review of articles comparing TIP in ICU beds who received end of life care following the imposition of a team of PC (intervention) to those who received care when they had not yet been introduced the PC team (control). The outcome measures were the time of ICU admission presented by average difference with the corresponding 95% CI, mortality in ICU presented as risk ratios with corresponding 95% CI and quality of life. Databases were searched: PUBMED, LILACS, Scopus, EMBASE and Cochrane CENTRAL. Results: After reading titles and abstracts of 399 articles, 27 studies were selected for full text analysis, and finally 19 were excluded, leaving 8 articles for inclusion, involving 7846 participants. Seven studies were performed in the United States and one in Australia. Meta-analysis was performed to the ICU length of stay, using four studies, which resulted in a reduction of approximately 2.5 days in the length of stay with the application of intervention: Media -2.44 days (CI -4.41 to -0 48) p = 0.01, I2 = 86%. It was also performed a meta-analysis of mortality in ICU with four studies, which resulted in lower mortality in the intervention group: hazard ratio = 0.78 (CI 0.70 to 0.87) p <0.00001, I2 = 18% , NNT = 23. There was no difference in quality of life. Conclusion: The installation CP teams can reduce suffering of family members and patients receiving end of life care in the ICU due to reduction of hospital stay and mortality rate in the ICU, which may first be costs reducer. Keywords: Palliative Care; End of Life Care; and Intensive Care Units.